(untitled) - Botkin, James W. (New York, 1984)
Going beyond the advances this country has made in the creation and marketing of high-technology products, this revolutionary new book offers a wide-ranging strategy for innovation in the American economy- one that will get us moving with the wave of the future as we integrate the economy of the past
Keywords: Công nghệ cao,Technological innovations,Đổi mới công nghệ,High technology; Hoa Kỳ,United States,Hoa Kỳ,United States